Pengaruh Konsentrasi Ekstrak Bunga Delima Merah (Punica granatum L.) Terhadap Hambatan Pertumbuhan Bakteri Streptococcus mutans (In Vitro) - Purnamasari, Ratih Dyah; , drg. Mahmud Kholifa, MDSc; , drg. Juwita Raditya Ningsih (2016)
Dental caries is an infectious disease caused by demineralization of enamel and dentin closely related to Streptococcus mutans bacterial activity. Dental caries could be mechanically and chemically prevented to decrease the activity of Streptococcus mutans. Long term usage of chemicals agents is considered to have any side effects, so that other alternatives that are safer and more natural, like a red pomegranate flower extract which has an antibacterial properties by containing any compounds such as: flavonoids, saponins, phenolic, proanthosianidin, and tannins. The aim of this study was to determine the antibacterial effect of red pomegranate flower extract against Streptococcus mutans and determine the concentration of red pomegranate flower extract solution which has an antibacterial properties as effective as positif control. This study was an experimental study using post test only control group design. Materials used in this study were red pomegranate flower extract with a concentration of 5%, 10%, 20%, 40%, 80%, with o,2% chlorhexidine gluconat as positive control and destilled water as negative control with four times repetition. The results of the study showed inhibition zone diameter of red pomegranate flower extract sequentially for concentration 5%, 10%, 20%, 40%, and 80% are 1,72 mm, 5,21 mm, 7,41 mm, 9,08 mm, and 13,14 mm. The treatment with Chlorhexidine gluconat 0,2% was about 10.42 mm, and aquades steril was about 0 mm. Based on these data after tested by One Way Anova generated p = 0.00 (p <0.05) so that the treatment with various concentrations of red pomegranate flower extract had a significant influence on the growth inhibition of bacteria Streptococcus mutans. Post Hoc LSD test showed a significant difference between the negative control (-) and in all concentration of red pomegranate flower extract (Punica granatum L.). It means that the red pomegranate flower extract (Punica granatum L.) has antibacterial activity against Streptococcus mutans. The mean of inhibition zone diameter concentration 80% (6.57 mm) is higher than zone of inhibition Chlorhexidine gluconat 0,2% as positive control (+)of 5.27 mm (p <0.05). The conclusion of the study that was wether the red pomegranate flower extract (Punica granatum L.) effect in inhibiting the growth of bacteria Streptococcus mutans and there were no similar antibacterial effect beetween of red pomegranate flower extract and positive control (+).